A novel benzothiazole derivative SKLB826 inhibits human hepatocellular carcinoma growth via inducing G2/M phase arrest and apoptosis. Issue 52 (10th June 2015) - Lei, Qian; Zhang, Lidan; Xia, Yong; Ye, Tinghong; Yang, Fangfang; Zhu, Yongxia; Song, Xuejiao; Wang, Ningyu; Xu, Ying; Liu, Xiaowei; Yu, Luoting
<x xml:space="preserve">Abstract</x> Hepatocellular carcinoma is the fifth most common cancer and durable responses in conventional treatments are limited so researchers have been devoted to developing new anti-HCC agents.